2016
DOI: 10.1016/j.tiv.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from soybean promotes cell proliferation in vitro

Abstract: Toxicological responses of exhaust emissions of biodiesel are different due to variation in methods of generation and the tested biological models. A chemical profile was generated using ICP-MS and GC-MS for the biodiesel samples obtained in Brazil. A cytotoxicity assay and cytokine secretion experiments were evaluated in human bronchial epithelial cells (BEAS-2B). Cells were exposed to polar (acetone) and nonpolar (hexane) extracts from particles obtained from fuel exhaust: fossil diesel (B5), pure soybean bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Therefore, it was concluded that the core and frit lipases were effective in the bioremediation of soybean oil wastes through transesterification ( Fig 9A and 9C ). The results of the transesterification reaction corroborate those found by other authors [ 32 ] who analyzed soybean oil samples modified through transesterification using ethanol and found increased BEAS-2B (human bronchial epithelial cells) proliferation. However, we suggest evaluating these effects on other cell lines since the skin tissue presents more types of cellular phenotypes than fibroblasts.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it was concluded that the core and frit lipases were effective in the bioremediation of soybean oil wastes through transesterification ( Fig 9A and 9C ). The results of the transesterification reaction corroborate those found by other authors [ 32 ] who analyzed soybean oil samples modified through transesterification using ethanol and found increased BEAS-2B (human bronchial epithelial cells) proliferation. However, we suggest evaluating these effects on other cell lines since the skin tissue presents more types of cellular phenotypes than fibroblasts.…”
Section: Discussionsupporting
confidence: 90%
“…8 The results of previous studies comparing the gaseous outputs of the two exhausts vary considerably. 4,9,38,39 The majority have found that biodiesel exhaust contains more NO x as well as a decrease in the average size of the particulate matter, 4,7,8 and this study has found similar results. Long-term exposure to NO x (made primarily of NO and NO 2 ) is associated with decreased lung volume, increased allergen response, and increased risk of respiratory infections.…”
Section: ■ Discussionsupporting
confidence: 77%
“…Combustion of both diesel and biodiesel results in the generation of toxic gases and respiratory irritants such as carbon dioxide, carbon monoxide, nitrogen oxides and sulfur dioxide . The results of previous studies comparing the gaseous outputs of the two exhausts vary considerably 4,9,33,34 . The majority have found that biodiesel exhaust contains more NOx as well as a decrease in the average size of the particulate matter 4,7,8 and this study has found similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jalava et al 2012) RME30(Jalava et al 2012) B20 (Bhavaruju et al 2014) B100(Gioda et al 2016) BD/Euro 1(Tzamkiozis et al 2010) 100 Soy(Finch et al 2002) Soy(Vogel et al 2019) Soy(Swanson et al 2009) Soy(Shvedova et al 2013) Animal(Vogel et al 2019) Hydro-treated(Vogel et al 2019) FAME(Yanamala et al 2013) RME(Jalava et al 2010(Jalava et al , 2012 RME(Cervena et al 2017;Libalova et al 2016; Novotna et al 2019) RME (Steiner et al 2013) HVO (Jalava et al 2010, 2012) NR (Kooter et al 2011) Fukagawa et al 2013) Soy (Vogel et al 2019) Soy (Bass et al 2015; Farraj et al 2015; Gavett et al 2015) Animal (Vogel et al 2019) Hydro-treated (Vogel et al 2019) NR (Bhavaraju et al 2014) Cooking oil (Traviss et al 2014) NR (Martin et al 2019) RME (Hemmingsen et al 2011) RME (Steiner et al 2013) AFME(Hemmingsen et al 2011) FAME(Kowalska et al 2017;Lankoff et al 2017;Magnusson et al 2017Magnusson et al , 2019Skuland et al 2017) FAME(Malorni et al 2017) FAME/HVO(Kowalska et al 2017; ;Lankoff et al 2017;Magnusson et al 2017Magnusson et al , 2019Skuland et al 2017) Australia Coconut(Vaughan et al 2019a;Vaughan et al 2019b) FAME(Mullins et al 2014) Australia Coconut(Vaughan et al 2019a) 7 RME(Andre et al 2015;Barraud et al 2017) FAME(Kowalska et al 2017; ;Lankoff et al 2017;Magnusson et al 2017Magnusson et al , 2019Skuland et al 2017) …”
mentioning
confidence: 99%